2022
DOI: 10.51253/pafmj.v72isuppl-2.3456
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients of Type 2 Diabetes Mellitus

Abstract: Objective: To document quality of life in type 2 diabetics and identify factors predictive of better quality of life. Study Design: Cross- sectional analytical study. Place and Duration of Study: Combined Military Hospital (CMH), Peshawar Pakistan, from Jul to Aug 2019. Methodology: Adult patients of either gender being treated in outdoor department for type 2 diabetes mellitus were enrolled using non- probability convenience sampling technique. We excluded unwilling patients, those with diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…15 On the contrary, in a study conducted by N Sarir et al in Pakistan in 2022 among 99 diabetic subjects, the scores of physical domain, psychological domain, social relationships and environmental domain indicated overall good quality of life. 16 In the present study, overall quality of life and general health score was lower in male diabetic subjects compared to female diabetic subjects. Domain scores of physical health, psychological domain and domain of social relationships were lower in male subjects.…”
Section: Discussioncontrasting
confidence: 41%
See 3 more Smart Citations
“…15 On the contrary, in a study conducted by N Sarir et al in Pakistan in 2022 among 99 diabetic subjects, the scores of physical domain, psychological domain, social relationships and environmental domain indicated overall good quality of life. 16 In the present study, overall quality of life and general health score was lower in male diabetic subjects compared to female diabetic subjects. Domain scores of physical health, psychological domain and domain of social relationships were lower in male subjects.…”
Section: Discussioncontrasting
confidence: 41%
“…23 On the contrary, in a study conducted by Sarir N et al in Pakistan in 2022 no association was found between duration of diabetes and quality of life. 16 Similarly, in a study conducted by Timar R et al in Romania in the year 2016 it was found that there was no significant association between quality of life of diabetic subjects and duration of disease. 19 In the present study overall quality of life and general health score was significantly lower in diabetic subjects with comorbidity (p value:0.038).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations